Current collector for heavy vehicles on electrified roads: kinematic analysis. (1st January 2014) - Aldammad, Mohamad; Ananiev, Anani; Kalaykov, Ivan
We present a prototype of a novel current collector manipulator to be mounted beneath a heavy vehicle to collect electric power from road embedded power lines. We describe the concept of the ground–level power supply system for heavy vehicles and its main components. The main requirements and constraints, such as safety, robustness to harsh road and weather operational conditions, ambient environment aspects and dynamic properties, are introduced. The emphasis is on the developed kinematic model, which provides the base for further development of the control system. We propose and derive an alternative approach for representing the inverse kinematics by a two–dimensional polynomial approximation that avoids the usage of complicated non–linear equations. It's simplicity is demonstrated by a numerical example with the basic parameters of the prototype. The basic motion sequences of the current collector and the way to control them are outlined.